Method for preparing carbon monoxide oxidation catalyst by using waste vanadium-titanium catalyst and electroplating sludge

By using a synergistic preparation method of waste vanadium-titanium catalysts and electroplating sludge, the problems of high cost and secondary pollution were solved, and efficient CO oxidation at low temperature was achieved, providing a green and economical catalyst preparation technology.

CN121338845AActive Publication Date: 2026-01-16SHAOXING UNIVERSITY

Patent Information

Application Number
CN202511896824.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-01-16
Estimated Expiration
2045-12-16

AI Technical Summary

Technical Problem

Existing CO oxidation catalysts are expensive and unsustainable in terms of resources. Traditional single solid waste utilization methods cannot simultaneously meet the requirements of activity, stability and cost, and there is a risk of secondary pollution.

Method used

A method for preparing carbon monoxide oxidation catalyst by synergistic use of waste vanadium-titanium catalyst and electroplating sludge is adopted. Through physicochemical treatments such as high-speed stirring, ultrasonic assistance, microwave activation, hydrothermal reaction and calcination, a complex multi-metal catalyst is formed.

Benefits of technology

Achieving efficient CO conversion at lower temperatures provides a green, low-carbon, and economical deep purification technology pathway for industrial exhaust gases. The catalyst exhibits significant oxidation effects and promising application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121338845A_ABST
    Figure CN121338845A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a carbon monoxide oxidation catalyst by using a waste vanadium-titanium catalyst and electroplating sludge, which realizes the mutual reaction of metal components in the electroplating sludge and components in the waste vanadium-titanium catalyst through the synergistic effect of various physical and chemical treatment methods and additives in the whole preparation process. The complex multi-metal catalyst can be used for photo-catalytic oxidation of carbon monoxide, has a remarkable oxidation effect and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of industrial solid waste resource utilization and high value, and particularly relates to a method for preparing carbon monoxide oxidation catalyst by using waste vanadium-titanium catalyst and electroplating sludge. BACKGROUND

[0002] The catalytic oxidation of carbon monoxide (CO) is a common key reaction in environmental catalysis, energy chemical industry and metallurgical tail gas treatment. Traditional CO oxidation catalysts are mostly composed of noble metals (Pt, Pd, Au, etc.) or transition metal oxides (Cu-Mn, Co-Ce, etc.), and their preparation process usually relies on high-purity chemical raw materials, resulting in high cost and unsustainable resources, and the abandoned catalyst itself becomes a new secondary solid waste. Therefore, developing a low-cost, high-activity and long-life CO oxidation catalyst based on industrial solid waste has important scientific and industrial significance for realizing “waste treatment with waste” and carbon emission reduction.

[0003] The waste vanadium-titanium catalyst is mainly derived from tail gas denitrification / sulfur removal devices in the processes of petroleum refining, sulfuric acid industry and coal chemical industry. Taking the sample provided by Hunan Yueyang Changxin New Material Co., Ltd. as an example, the typical chemical composition thereof contains V2O5, TiO2, WO3, SiO2, Al2O3, etc. Vanadium (V) has multiple valence states (V 5+ / V 4+ / V 3+ ) cyclic ability, and is a recognized redox active center; TiO2 (anatase / rutile) is not only an excellent carrier, but also can generate strong mutual interaction (SMSI) through V–O–Ti interface to promote oxygen vacancy generation and migration; WO3 can improve the thermal stability and sulfur poisoning resistance of the catalyst. The solid waste also contains a certain amount of SiO2, Al2O3 and Fe2O3, which can form mullite, ilmenite and other inert skeletons in the subsequent calcination process to inhibit the sintering of the active components. The electroplating sludge is generated in the lime-iron salt co-precipitation treatment process of electroplating wastewater, and is one of the largest heavy metal hazardous wastes at present. Taking the sample provided by Guangdong Shenzhen Greenmax Materials Co., Ltd. as an example, the main components thereof include Fe2O3, Cr2O3, NiO, ZnO, CuO and Al2O3, and the rest are inevitable impurities and loss on ignition. The electroplating sludge is rich in transition metals such as Cr, Ni, Cu and Zn, and the oxides thereof can form spinel, perovskite and other structures under appropriate atmosphere, which have intrinsic redox activity; Fe2O3 can act as an oxygen carrier to participate in CO oxidation through Fe 3+ / Fe 2+ cycle; CaO and SiO2 act as bonding and structural additives to improve the mechanical strength of the catalyst.

[0004] Traditional CO oxidation catalysts usually use high-purity V2O5, TiO2, noble metal salts and other chemical products, which have high cost. The waste vanadium-titanium catalyst and electroplating sludge are mainly stored, co-disposed in cement kiln or recovered by pyrometallurgy, which has low added value and secondary pollution risk. Single solid waste is often difficult to meet the requirements of activity, stability and cost at the same time, and existing researches focus on single solid waste utilization, ignoring the synergistic activation potential between multiple solid wastes. The composition of solid waste fluctuates greatly, and the traditional impregnation-calcination process is difficult to accurately control the active phase structure, resulting in poor performance reproducibility and short service life. SUMMARY

[0005] In view of the above background, the present application proposes a new idea of "co-preparing CO oxidation catalysts from waste vanadium-titanium catalysts and electroplating sludge", which not only solves the problem of high-value utilization of two typical hazardous wastes, but also obtains a high-performance catalyst that can efficiently convert CO at a relatively low temperature (below 150°C), providing a green, low-carbon and economic technical path for industrial tail gas deep purification. Therefore, the purpose of the present application is to provide a method for preparing carbon monoxide oxidation catalysts from waste vanadium-titanium catalysts and electroplating sludge.

[0006] TECHNICAL SOLUTION: In order to solve the above technical problems, the present application provides a method for preparing carbon monoxide oxidation catalysts from waste vanadium-titanium catalysts and electroplating sludge, comprising the following steps:

[0007] (1) Weighing the waste vanadium-titanium catalyst and the electroplating sludge, and placing them in a stirrer to fully mix and evenly mix them to obtain a mixed slurry;

[0008] (2) Mixing the mixed slurry with a sulfuric acid solution, ultrasonicating in an ultrasonic cleaner, then standing and settling, separating the upper clear liquid, and obtaining the acid activated slag as the sediment;

[0009] (3) Mixing the acid activated slag with a sodium hydroxide solution, stirring and reacting to obtain an alkali treated slag;

[0010] (4) Placing the alkali treated slag in a microwave reactor for microwave activation treatment to obtain a microwave activated alkali treated slag;

[0011] (5) Weighing the plant extract and the microwave activated alkali treated slag, stirring them evenly, then transferring the mixture to a hydrothermal reaction kettle for hydrothermal reaction to obtain a hydrothermal activated material;

[0012] (6) Washing the hydrothermal activated material with deionized water until it is neutral, then performing suction filtration separation, then placing the filter cake in a drying box to dry to obtain a dried hydrothermal activated powder, and placing the dried hydrothermal activated powder in a molding equipment to press and form into a catalyst blank with certain shape and strength;

[0013] (7) placing the catalyst blank in a tube furnace, and performing calcination under an air atmosphere to obtain a carbon monoxide oxidation catalyst material.

[0014] The mass ratio of the waste vanadium-titanium catalyst to the electroplating sludge in step (1) is 40-60:100.

[0015] The stirring speed in step (1) is 500-2500 r / min, and the stirring time is 20-60 minutes.

[0016] The concentration of the sulfuric acid solution in step (2) is 2-4 M, and the liquid-solid ratio of the sulfuric acid solution to the mixed slurry is 0.4-0.6:1 (mL / g).

[0017] The ultrasonic frequency in step (2) is 35-45 kHz, the ultrasonic-assisted stirring time is 30-40 minutes, and then the settling time is 1.5-2.5 hours.

[0018] The concentration of the sodium hydroxide solution in step (3) is 4-8 M, the liquid-solid ratio of the sodium hydroxide solution to the acid active slag is 0.4-0.8:1 (mL / g), and the stirring reaction time is 2-4 hours.

[0019] The microwave power in step (4) is 400-600 W, and the microwave time is 5-15 minutes.

[0020] The mass ratio of the plant extract to the microwave-activated alkali residue in step (5) is 0.5-2.5:100, the hydrothermal reaction temperature is 180-220°C, and the hydrothermal reaction time is 8-12 hours.

[0021] The drying temperature in step (6) is 60-120°C, and the drying time is 5-15 hours.

[0022] The calcination temperature in step (7) is 550-750°C, and the calcination time is 4-6 hours.

[0023] Reaction mechanism of the present application: The present application can make the waste vanadium-titanium catalyst and electroplating sludge fully mixed and uniform by high-speed stirring, and the particles collide and disperse with each other. Sulfuric acid as an acid leaching agent reacts with part of metal oxides in the waste vanadium-titanium catalyst and electroplating sludge in the acidic environment, so that it is dissolved into the liquid phase to form the corresponding sulfate. Ultrasonic-assisted stirring helps to destroy the boundary layer on the surface of the particles and accelerate the mass transfer process of the reactants to the surface of the particles. Sodium hydroxide as an alkali leaching agent further reacts with the metal oxides or their sulfates in the acid leaching residue, converting some metal components that are not completely dissolved or in a form that is not easy to utilize during the acid leaching process into soluble salts or forms that are easier to handle. Stirring reaction enables the alkali solution to fully contact with the solid particles, promoting the reaction to proceed and obtaining the alkali treatment residue. The rapid and uniform heating effect of microwave energy intensifies the movement of ions or atoms inside the metal compounds in the alkali treatment residue, destroys the crystal structure or causes phase transition, thereby increasing its activity and reactivity. At the same time, the microwave also initiates some local high-temperature and high-pressure environment, promotes the occurrence of certain chemical reactions, changes the surface properties and microstructure of the residue, forms active sites that are beneficial to subsequent hydrothermal reactions, and obtains microwave-activated alkali residue. The hydrothermal reaction provides a high-temperature and high-pressure closed environment, so that the reaction system can carry out deep chemical reactions under relatively mild conditions. The organic components in the plant extract fully contact and mix with the inorganic components in the microwave-activated alkali residue under hydrothermal conditions, and undergo substance exchange and chemical reaction to form a composite material with specific structure and performance. In this process, the plant extract not only participates in the chemical reaction as a reactant, but also may act as a regulator and stabilizer to control the morphology and size of the product, and finally obtain a hydrothermal-activated material. By fully washing with deionized water, the residual acid, alkali and other soluble impurities in the hydrothermal-activated material are removed to avoid the influence of these impurities on the performance of the subsequent catalyst. Under the high-temperature calcination environment, the organic components in the material are oxidized and decomposed, and part of the metal compounds undergoes oxidation-reduction reaction or crystal type transition, so that the structure of the catalyst is more compact and stable, the dispersion degree of the active components is increased, and the active sites are more fully exposed, and finally a carbon monoxide oxidation catalyst material is obtained.

[0024] Advantages: Compared with the prior art, the present application has the following advantages: The present application realizes the mutual reaction of the metal components in the electroplating sludge and the components in the waste vanadium-titanium catalyst through the synergistic effect of various physical and chemical treatment methods and additives in the whole preparation process, forms a complex multi-metal catalyst, which can be used for photocatalytic oxidation of carbon monoxide, has a significant oxidation effect, and has a good application prospect. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 Flow chart of the treatment method of the present application. DETAILED DESCRIPTION

[0026] The application will be further described below in conjunction with the accompanying drawings and examples.

[0027] Spent vanadium-titanium catalyst: provided by Hunan Yueyang Changxin New Material Co., Ltd., and the main detected components include: 41.26% V2O5, 28.54% TiO2, 11.38% WO3, 7.72% SiO2, 3.65% Al2O3, 2.04% Fe2O3, 1.52% Na2O, 0.71% CaO, 0.53% SO3 and other components (unavoidable impurities and loss on ignition);

[0028] Electroplating sludge: provided by Guangdong Shenzhen Greenmax Technologies Co., Ltd., and the main components include Fe2O3, Cr2O3, NiO, ZnO, CuO, Al2O3 and the rest are unavoidable impurities and loss on ignition.

[0029] Preparation of aloe extract: take the gel scraped from the leaves of three-year-old aloe and immediately mix with color protection liquid containing 0.08% vitamin C at a volume ratio of 1:1; the gel slurry is broken after high-pressure homogenization (pressure 90 MPa), and impurities are removed through a 0.22 μm ceramic microfiltration membrane; the permeate is vacuum concentrated to 1 / 3 of the original volume at 42°C, 4 times the volume of 95% ethanol is added to precipitate polysaccharides, and after 7 hours of standing, centrifugation is performed; the precipitate is redissolved with deionized water, separated through a 50 kDa ultrafiltration membrane, and the high molecular weight polysaccharide solution is collected, freeze-dried (-50°C, vacuum 8 Pa) to obtain aloe polysaccharide, the final product has a polysaccharide content of 45%, an O-acetyl content of 6.2% and a free anthraquinone content of 0.3 ppm.

[0030] Preparation of malva extract: malva flowers are dried in the shade to a moisture content of 8%, ground through a 30 mesh sieve, and added with deionized water at pH 6.8 at a solid-liquid ratio of 1:18 (g / mL), extracted at 55°C under ultrasonic power of 250 W for 50 minutes, and repeated twice; the extraction liquid is filtered through 200 mesh filter cloth, vacuum concentrated to 1 / 5 of the original volume at 50°C, and 95% ethanol is slowly added under stirring until the alcohol concentration reaches 72%, and the mixture is left to stand at 4°C for 18 hours, and the precipitate is freeze-dried after centrifugation; the supernatant is recovered after ethanol removal, and the total flavone fraction is obtained by AB-8 macroporous resin adsorption and elution with 60% ethanol, and the whole process is operated in the dark, and the final product has a total flavone content of 18% and a polysaccharide content of 35%.

[0031] Preparation of rosemary extract: Fresh rosemary leaves were frozen in liquid nitrogen and ground to 0.8 mm in size. The material was added to a buffer solution (pH 4.8) containing 0.8% cellulase and pectinase at a ratio of 1:9. Enzymolysis was performed at 48°C for 100 minutes. Then, 95% ethanol was added to the system to a final concentration of 65%, and the system was heated to 65°C for 1.8 hours of reflux extraction. After the extraction solution was cooled, it was centrifuged at 4500 rpm to obtain the supernatant. The supernatant was concentrated at 45°C under reduced pressure until the alcohol odor disappeared. The water phase was extracted with ethyl acetate three times, and the water phase was purified by a polyamide column. The fraction containing rosemary acid and carnosic acid was collected and spray dried (inlet temperature 170°C, outlet temperature 75°C). The final product had a lipoxygenase inhibition rate of 88% and a total phenol content of 28%.

[0032] Preparation of chamomile flower extract: The flower heads at the initial flowering stage were air-dried at 37°C to a water content of 7%, ground to pass through a 10-mesh sieve, and added to deionized water at a ratio of 1:22. The pH was adjusted to 5.2 with citric acid, and 0.4% β-glucosidase was added. Enzymolysis was performed at 43°C for 75 minutes. Then, the system was heated to 105°C under nitrogen protection for 18 minutes of subcritical water extraction, with the pressure controlled at 0.2 MPa. After the extraction solution was cooled to 20°C, it was centrifuged. The supernatant was adsorbed by a macroporous resin XAD-7HP, and impurities were removed by elution with 25% ethanol. The flavonoid fraction was obtained by elution with 65% ethanol. The eluate was concentrated at 37°C under vacuum and then freeze-dried. The whole process was carried out in the dark under nitrogen protection. The final product had a matricaria chrysoindole content of 0.35% and a total flavonoid content of 20%.

[0033] Preparation of hyacinth extract: The hyacinth bulbs were peeled and dried by heat pump at 45°C. The dried bulbs were ground to 70 mesh and added to 70% ethanol at a ratio of 1:12. Ultrasonic treatment was performed at a power of 300 W and a temperature of 50°C for 40 minutes. Ammonium sulfate was added to the extraction solution to a concentration of 18% (w / v) to form a two-water phase system. The ethanol layer in the upper phase was taken after the system was allowed to stand for 30 minutes. The ethanol layer was concentrated to near dryness at 40°C under reduced pressure. The residue was redissolved in deionized water and purified by a D101 macroporous resin. The eluate was concentrated and then freeze-dried. The final product had a total flavonoid content of 14%, an alkaloid content of 0.08%, and no irritating residue.

[0034] Example 1 Effect of the mass ratio of spent vanadium-titanium-based catalyst to electroplating sludge on the performance of a prepared carbon monoxide oxidation catalyst

[0035] The waste vanadium-titanium catalyst and electroplating sludge were weighed according to the mass ratio of 25:100, 30:100, 35:100, 40:100, 50:100, 60:100, 65:100, 70:100, and 75:100 respectively, and were placed in a stirrer to stir at a speed of 500 r / min for 20 minutes to fully mix and evenly distribute the two. Nine groups of mixed slurry were obtained. The nine groups of mixed slurry were mixed with nine groups of 2M sulfuric acid solution, with a liquid-solid ratio of 0.4:1 (mL / g). Ultrasonic assisted stirring was performed in an ultrasonic cleaner for 30 minutes at an ultrasonic frequency of 35 kHz, followed by standing and settling for 1.5 hours. The upper clear liquid was separated, and nine groups of acid activated slag were obtained. The nine groups of acid activated slag were mixed with nine groups of 4M sodium hydroxide solution, with a liquid-solid ratio of 0.4:1 (mL / g), and stirred for 2 hours to obtain nine groups of alkali treated slag. The nine groups of alkali treated slag were placed in a microwave reactor, and the microwave power was set to 400W and the microwave time was 5 minutes for microwave activation treatment, to obtain nine groups of microwave activated alkali treated slag. According to the mass ratio of 0.5:100, nine groups of plant extracts and nine groups of microwave activated alkali treated slag were weighed and stirred evenly, and then the mixture was transferred to a hydrothermal reactor, with a hydrothermal temperature of 180°C and a hydrothermal time of 8 hours to obtain nine groups of hydrothermal activated materials, wherein the plant extract was aloe extract. The nine groups of hydrothermal activated materials were washed with deionized water until neutral, then subjected to suction filtration separation, and then the filter cake was placed in a drying oven at 60°C for 5 hours to obtain nine groups of dried hydrothermal activated powder. The nine groups of dried hydrothermal activated powder were placed in a molding equipment and pressed into a certain shape and strength under a pressure of 20MPa to obtain nine groups of catalyst blanks. The nine groups of catalyst blanks were placed in a tube furnace and calcined in an air atmosphere, with a calcination temperature of 550°C and a calcination time of 4 hours to obtain nine groups of carbon monoxide oxidation catalyst materials.

[0036] Carbon monoxide oxidation test: at room temperature (25 ± 1°C), nine groups of carbon monoxide oxidation catalyst materials prepared by 185nm vacuum ultraviolet light (VUV) excitation were used to oxidize CO to CO2. The vacuum ultraviolet lamp was a low-pressure mercury lamp (L-type quartz window, 185nm output ≥5mW·cm-2, 254nm cutoff filter optional); the photo-reactor was a cylindrical high-purity quartz tube with an effective optical path L=10.0cm, an inner diameter d=2.0cm, and a volume V=31.4mL; the vacuum system was a turbo molecular pump with a cold trap (limit vacuum <1×10-5Pa); after the reactor was evacuated, a mixed gas (CO:O2:N2=1:1:8 (volume ratio), CO initial concentration C0≈100ppm) was injected at a set total pressure P total =101kPa, the inlet and outlet valves were closed, and the initial concentration C CO,0 was recorded after standing for 5min. -2 -3 total CO,0CO,0 , C CO2,0 , the VUV lamp was turned on and the time was started. The CO and CO2 concentrations were recorded continuously with a sampling frequency of 1 Hz; the reaction time t = 0 ~ 30 min (preliminary experiments showed that the reaction tended to equilibrium within 30 min). The lamp power was maintained constant, the incident light intensity I0was measured with an ultraviolet radiation meter (probe 185 nm); the temperature and pressure were recorded every min, ensuring that T = 25 ± 1 °C and P change < 1%. The lamp was turned off, and the gas in the reactor was immediately extracted to determine the final concentration C CO,t , C CO2,t ; the possible water was captured with a cold trap, and gas chromatography-thermal conductivity detection (GC-TCD) was used to verify that there were no other carbon-containing products, the experiment was repeated 3 times, and the average value was taken. The ppm values (C CO,0 and C CO,t ) measured by the online analyzer were converted to molar fractions y (y CO,0 and y CO,t ), the number of moles of gas in the reactor n = PV / (RT), where T = 298.15 K, the carbon monoxide oxidation efficiency η = (y CO,0 – y CO,t ) / y CO,0 × 100%.

[0037] The test results of this example are shown in Table 1.

[0038] Table 1 Influence of the mass ratio of waste vanadium-titanium catalyst to electroplating sludge on the performance of the prepared carbon monoxide oxidation catalyst Spent vanadium-titanium catalyst to electroplating sludge mass ratio Carbon monoxide oxidation efficiency Relative error percentage 25:100 79.52% ±0.2% 30:100 83.49% ±0.1% 35:100 86.37% ±0.1% 40:100 90.75% ±0.1% 50:100 92.16% ±0.1% 60:100 94.01% ±0.1% 65:100 90.28% ±0.1% 70:100 87.84% ±0.2% 75:100 85.93% ±0.1%

[0039] As can be seen from Table 1, when the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is less than 40:100 (for example, the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is 35:100, 30:100, 25:100 in Table 1, and lower ratios not listed in Table 1), the waste vanadium-titanium catalyst is added less, and the reaction between the waste vanadium-titanium catalyst and the electroplating sludge is insufficient, resulting in a significant decrease in the carbon monoxide oxidation efficiency as the mass ratio of waste vanadium-titanium catalyst to electroplating sludge decreases. When the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is equal to 40-60:100 (for example, the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is 40:100, 50:100, 60:100 in Table 1), the waste vanadium-titanium catalyst mainly contains vanadium, titanium and other elements in the form of vanadium oxide and titanium oxide. The electroplating sludge has complex composition and contains various metals and their compounds, such as metal hydroxides or oxides of iron, copper, nickel, and some organic matter and inorganic salts. Through high-speed stirring, the waste vanadium-titanium catalyst and the electroplating sludge can be fully mixed and uniformly dispersed, and the particles can collide and disperse with each other. Sulfuric acid as an acid leaching agent reacts with part of the metal oxides in the waste vanadium-titanium catalyst and the electroplating sludge in an acidic environment, dissolves into the liquid phase, and forms the corresponding sulfate. Ultrasonic-assisted stirring helps to destroy the boundary layer on the surface of the particles and accelerate the mass transfer process of the reactants to the surface of the particles. Finally, the carbon monoxide oxidation efficiency is higher than 90%. When the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is greater than 60:100 (for example, the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is 65:100, 70:100, 75:100 in Table 1, and higher ratios not listed in Table 1), the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is too high, the waste vanadium-titanium catalyst is added in excess, and the reaction between the waste vanadium-titanium catalyst and the electroplating sludge is unbalanced, resulting in a significant decrease in the carbon monoxide oxidation efficiency as the mass ratio of waste vanadium-titanium catalyst to electroplating sludge further increases. Therefore, in general, when the mass ratio of waste vanadium-titanium catalyst to electroplating sludge is equal to 40-60:100, it is most beneficial to improve the oxidation performance of the prepared catalyst for CO in terms of benefits and costs.

[0040] Example 2 Influence of liquid-solid ratio of sulfuric acid solution to mixed slurry on performance of prepared carbon monoxide oxidation catalyst

[0041] The waste vanadium-titanium catalyst and electroplating sludge were weighed according to a mass ratio of 60:100, placed in a stirrer, and stirred at a speed of 1500 r / min for 40 min to fully mix and evenly distribute the two materials, obtaining a mixed slurry. The mixed slurry was mixed with a sulfuric acid solution with a concentration of 3 M, and the liquid-solid ratio was controlled at 0.25:1 (mL / g), 0.3:1 (mL / g), 0.35:1 (mL / g), 0.4:1 (mL / g), 0.5:1 (mL / g), 0.6:1 (mL / g), 0.65:1 (mL / g), 0.7:1 (mL / g), and 0.75 (mL / g), respectively. Ultrasonic-assisted stirring was performed in an ultrasonic cleaner for 35 min at an ultrasonic frequency of 40 kHz, followed by standing for 2 h, and the supernatant was separated, obtaining nine groups of acid active residues. The nine groups of acid active residues were mixed with a sodium hydroxide solution with a concentration of 6 M, and the liquid-solid ratio was 0.6:1 (mL / g), and stirring was performed for 3 h, obtaining nine groups of alkali-treated residues. The nine groups of alkali-treated residues were placed in a microwave reactor, and microwave activation treatment was performed at a microwave power of 500 W for 10 min, obtaining nine groups of microwave-activated alkali-treated residues. Plant extracts and the nine groups of microwave-activated alkali-treated residues were weighed according to a mass ratio of 1.5:100, and stirring was performed, and then the mixture was transferred to a hydrothermal reactor, and the hydrothermal temperature was set to 200 ℃, and the hydrothermal time was 10 h, obtaining nine groups of hydrothermal activated materials, wherein the plant extracts were malva sylvestris extracts. The nine groups of hydrothermal activated materials were washed with deionized water until neutral, and then were separated by suction filtration, and then the filter cake was placed in a drying oven and dried at 90 ℃ for 10 h, obtaining nine groups of dried hydrothermal activated powders. The nine groups of dried hydrothermal activated powders were placed in a molding device and molded under a pressure of 25 MPa, obtaining catalyst blanks with certain shapes and strengths. The catalyst blanks were placed in a tube furnace and calcined in an air atmosphere, and the calcination temperature was set to 650 ℃, and the calcination time was 5 h, obtaining nine groups of carbon monoxide oxidation catalyst materials.

[0042] The carbon monoxide oxidation test and the calculation of the carbon monoxide oxidation efficiency were the same as in Example 1, and the test results of this example are shown in Table 2.

[0043] Table 2 Influence of liquid-solid ratio of sulfuric acid solution and mixed slurry on performance of prepared carbon monoxide oxidation catalyst Sulfuric acid solution to mixed slurry liquid to solid ratio Carbon monoxide oxidation efficiency Relative error percentage 0.25:1 (mL / g) 86.71% ±0.1% 0.3:1 (mL / g) 88.32% ±0.1% 0.35:1 (mL / g) 90.85% ±0.1% 0.4:1 (mL / g) 94.29% ±0.1% 0.5:1 (mL / g) 95.38% ±0.1% 0.6:1 (mL / g) 96.91% ±0.1% 0.65:1 (mL / g) 93.43% ±0.2% 0.7:1 (mL / g) 91.58% ±0.1% 0.75 (mL / g) 89.74% ±0.1%

[0044] As can be seen from Table 2, when the liquid-solid ratio of sulfuric acid solution to mixed slurry is less than 0.4:1 (mL / g) (for example, the liquid-solid ratio of sulfuric acid solution to mixed slurry = 0.35:1 (mL / g), 0.3:1 (mL / g), 0.25:1 (mL / g) in Table 2, and lower ratios not listed in Table 2), less sulfuric acid solution is added, and the reaction between the sulfuric acid solution and the mixed slurry is insufficient, resulting in a significant decrease in the carbon monoxide oxidation efficiency as the liquid-solid ratio of sulfuric acid solution to mixed slurry decreases. When the liquid-solid ratio of sulfuric acid solution to mixed slurry is equal to 0.4-0.6:1 (mL / g) (for example, the liquid-solid ratio of sulfuric acid solution to mixed slurry = 0.4:1 (mL / g), 0.5:1 (mL / g), 0.6:1 (mL / g) in Table 2), sulfuric acid as an acid leaching agent reacts with part of the metal oxides in the waste vanadium-titanium catalyst and electroplating sludge in an acidic environment, causing them to dissolve into the liquid phase to form corresponding sulfates. Ultrasonic-assisted stirring helps to break the boundary layer on the surface of the particles and accelerate the mass transfer process of the reactants to the surface of the particles. Ultimately, the carbon monoxide oxidation efficiency is higher than 90%. When the liquid-solid ratio of sulfuric acid solution to mixed slurry is greater than 0.6:1 (mL / g) (for example, the liquid-solid ratio of sulfuric acid solution to mixed slurry = 0.65:1 (mL / g), 0.7:1 (mL / g), 0.75 (mL / g) in Table 2, and higher ratios not listed in Table 2), the liquid-solid ratio of sulfuric acid solution to mixed slurry is too high, and the sulfuric acid solution is added in excess, resulting in an imbalance in the reaction between the sulfuric acid solution and the mixed slurry, which leads to a significant decrease in the carbon monoxide oxidation efficiency as the liquid-solid ratio of sulfuric acid solution to mixed slurry further increases. Therefore, in general, when the liquid-solid ratio of sulfuric acid solution to mixed slurry is equal to 0.4-0.6:1 (mL / g), it is most beneficial to improve the carbon monoxide oxidation performance of the prepared catalyst in terms of benefits and costs.

[0045] Example 3 Effect of plant extract and microwave-activated alkali residue mass ratio on the performance of the prepared carbon monoxide oxidation catalyst

[0046] The waste vanadium-titanium catalyst and electroplating sludge were weighed according to a mass ratio of 60:100, put into a stirrer, and stirred at a speed of 2500 r / min for 60 min to make them fully mixed and uniform, to obtain a mixed slurry. The mixed slurry was mixed with a sulfuric acid solution with a concentration of 4 M, and the liquid-solid ratio was controlled at 0.6:1 (mL / g). The mixture was subjected to ultrasonic-assisted stirring in an ultrasonic cleaner for 40 min at an ultrasonic frequency of 45 kHz, and then was left to stand for 2.5 h. The supernatant was separated, and the obtained sediment was an acid active residue. The acid active residue was mixed with a sodium hydroxide solution with a concentration of 8 M, and the liquid-solid ratio was 0.8:1 (mL / g). The mixture was stirred for 4 h to obtain an alkali-treated residue. The alkali-treated residue was subjected to microwave activation treatment in a microwave reactor, with a microwave power of 600 W and a microwave time of 15 min, to obtain a microwave-activated alkali-treated residue. The plant extract and the microwave-activated alkali-treated residue were weighed according to mass ratios of 0.25:100, 0.3:100, 0.4:100, 0.5:100, 1.5:100, 2.5:100, 2.75:100, 3:100, and 3.25:100, respectively, and were stirred uniformly. Then, the mixture was transferred into a hydrothermal reactor, and the hydrothermal temperature was set at 220 ℃. The hydrothermal time was 12 h, to obtain nine groups of hydrothermal activated materials, wherein the plant extract was rosemary extract. The nine groups of hydrothermal activated materials were washed with deionized water until neutral, and then were subjected to suction filtration. Subsequently, the filter cake was placed in a drying oven, and was dried at 120 ℃ for 15 h, to obtain nine groups of dried hydrothermal activated powders. The nine groups of dried hydrothermal activated powders were placed in a molding device, and were pressed into catalyst blanks under a pressure of 30 MPa. The nine groups of catalyst blanks were placed in a tube furnace, and were calcined in an air atmosphere. The calcination temperature was set at 750 ℃, and the calcination time was 6 h, to obtain nine groups of carbon monoxide oxidation catalyst materials.

[0047] The carbon monoxide oxidation test and the calculation of the carbon monoxide oxidation efficiency were the same as in Example 1. The test results of this example are shown in Table 3.

[0048] Table 3 Influence of the mass ratio of plant extract and microwave-activated alkali-treated residue on the performance of the prepared carbon monoxide oxidation catalyst Plant extract and microwave-activated base residue mass ratio Carbon monoxide oxidation efficiency Relative error percentage 0.25:100 89.92% ±0.1% 0.3:100 90.56% ±0.1% 0.4:100 92.15% ±0.2% 0.5:100 96.97% ±0.1% 1.5:100 97.36% ±0.1% 2.5:100 98.02% ±0.1% 2.75:100 96.41% ±0.1% 3:100 93.95% ±0.1% 3.25:100 92.79% ±0.2%

[0049] As shown in Table 3, when the mass ratio of plant extract to microwave-activated alkali residue is less than 0.5:100 (e.g., in Table 3, the mass ratios of plant extract to microwave-activated alkali residue are 0.4:100, 0.3:100, 0.25:100, and even lower ratios not listed in Table 3), the addition of plant extract is insufficient, resulting in incomplete reaction between the plant extract and the microwave-activated alkali residue. Consequently, the carbon monoxide oxidation efficiency decreases significantly as the mass ratio of plant extract to microwave-activated alkali residue decreases. When the mass ratio of plant extract to microwave-activated alkali residue is equal to 0.5~2.5:100 (e.g., in Table 3, the mass ratios of plant extract to microwave-activated alkali residue are 0.5:100, 1.5:100, and 2.5:100), the organic components in the plant extract and the inorganic components in the microwave-activated alkali residue fully contact and mix under hydrothermal conditions, undergoing mass exchange and chemical reactions to form a composite material with specific structure and properties. In this process, plant extracts not only participate in the chemical reaction as reactants but also act as regulators and stabilizers, controlling the morphology and size of the products, ultimately yielding a hydrothermally activated material. Thorough rinsing with deionized water removes residual acids, alkalis, and other soluble impurities from the hydrothermally activated material, preventing these impurities from affecting the subsequent catalyst performance. Under high-temperature calcination, the organic components in the material undergo oxidative decomposition, and some metal compounds undergo redox reactions or crystal transformations, resulting in a more compact and stable catalyst structure, increased dispersion of active components, and more complete exposure of active sites, ultimately yielding a carbon monoxide oxidation catalyst material. Ultimately, the carbon monoxide oxidation efficiency is higher than 96%. When the mass ratio of plant extract to microwave-activated alkaline residue is greater than 2.5:100 (as shown in Table 3, the mass ratios of plant extract to microwave-activated alkaline residue are 2.75:100, 3:100, 3.25:100, and higher ratios not listed in Table 3), the excessively high mass ratio of plant extract to microwave-activated alkaline residue leads to an imbalance in the reaction between the plant extract and the residue, resulting in a significant decrease in carbon monoxide oxidation efficiency as the mass ratio of plant extract to microwave-activated alkaline residue further increases. Therefore, considering both benefits and costs, a mass ratio of plant extract to microwave-activated alkaline residue of 0.5~2.5:100 is most favorable for improving the CO oxidation performance of the prepared catalyst.

[0050] Example 4: Effect of plant extracts on the performance of the prepared carbon monoxide oxidation catalyst

[0051] Waste vanadium-titanium catalyst and electroplating sludge were weighed at a mass ratio of 40:100 and placed in a mixer. The mixture was stirred at 2500 rpm for 40 minutes to ensure thorough mixing and obtain a slurry. The slurry was then mixed with a 4M sulfuric acid solution, maintaining a liquid-to-solid ratio of 0.6:1 (mL / g). The mixture was ultrasonically stirred for 40 minutes at a frequency of 45 kHz in an ultrasonic cleaner, followed by settling for 2.5 hours. The supernatant was separated, and the resulting sludge was identified as acid-activated sludge. This acid-activated sludge was then mixed with an 8M sodium hydroxide solution at a liquid-to-solid ratio of 0.6:1 (mL / g) and stirred for 3 hours to obtain alkali-treated sludge. This alkali-treated sludge was placed in a microwave reactor, and microwave activation was performed at a power of 600W for 15 minutes to obtain microwave-activated alkali-treated sludge. Plant extracts and microwave-activated alkali treatment residue were weighed at a mass ratio of 2.5:100, stirred evenly, and then the mixture was transferred to a hydrothermal reactor. The hydrothermal temperature was set at 220℃ and the hydrothermal time was 12 hours, resulting in five groups of hydrothermally activated materials, with the plant extracts being one of aloe vera extract, mallow extract, rosemary extract, chamomile extract, and hyacinth extract. The five groups of hydrothermally activated materials were thoroughly washed with deionized water until neutral, and then separated by suction filtration. The filter cake was then placed in a drying oven and dried at 120℃ for 15 hours to obtain five groups of dried hydrothermally activated powders. The five groups of dried hydrothermally activated powders were placed in a molding device and pressed into shape under a pressure of 30MPa to obtain five groups of catalyst blanks with certain shapes and strengths. The catalyst blanks were placed in a tube furnace and calcined in an air atmosphere. The calcination temperature was set at 750℃ and the calcination time was 6 hours to obtain five groups of carbon monoxide oxidation catalyst materials.

[0052] The carbon monoxide oxidation test and carbon monoxide oxidation efficiency calculation were the same as in Example 1. The test results of this example are shown in Table 4.

[0053] Table 4. Effects of plant extracts on the performance of the prepared carbon monoxide oxidation catalyst. Plant extract Carbon monoxide oxidation efficiency Relative error percentage Aloe extract 97.02% ±0.1% Malva extract 97.31% ±0.1% Rosemary extract 97.29% ±0.1% Chamomile extract 96.98% ±0.1% Hyacinth extract 97.15% ±0.1%

[0054] As shown in Table 4, when the plant extract is any one of aloe vera extract, mallow extract, rosemary extract, chamomile extract, or hyacinth extract, the oxidation performance of the prepared catalyst for CO is not significantly different.

[0055] The effect of different processes on the performance of the prepared carbon monoxide oxidation catalyst

[0056] The process of this invention is as follows: Waste vanadium-titanium catalyst and electroplating sludge are weighed at a mass ratio of 60:100 and placed in a mixer. The mixture is stirred at 2500 r / min for 40 minutes to ensure thorough and uniform mixing, resulting in a slurry. This slurry is then mixed with a 3M sulfuric acid solution, maintaining a liquid-to-solid ratio of 0.6:1 (mL / g). The mixture is then ultrasonically stirred for 40 minutes at a frequency of 45 kHz in an ultrasonic cleaner. Afterward, it is allowed to settle for 2 hours, and the supernatant is separated, yielding an acid-activated sludge. This acid-activated sludge is mixed with an 8M sodium hydroxide solution at a liquid-to-solid ratio of 0.6:1 (mL / g) and stirred for 3 hours to obtain an alkali-treated sludge. The alkali-treated sludge is placed in a microwave reactor, and microwave activation is performed at a power of 600W for 15 minutes to obtain microwave-activated alkali-treated sludge. Plant extract and microwave-activated alkali treatment residue were weighed at a mass ratio of 2.5:100, stirred evenly, and then the mixture was transferred to a hydrothermal reactor. The hydrothermal temperature was set at 220℃ and the hydrothermal time was 12 hours to obtain a hydrothermally activated material, wherein the plant extract was hyacinth extract. The hydrothermally activated material was thoroughly washed with deionized water until neutral, and then filtered. The filter cake was then placed in a drying oven and dried at 60℃ for 5 hours to obtain a dried hydrothermally activated powder. The dried powder was placed in a molding device and pressed into shape under a pressure of 30MPa to obtain a catalyst preform with a certain shape and strength. The catalyst preform was placed in a tube furnace and calcined in an air atmosphere. The calcination temperature was set at 750℃ and the calcination time was 6 hours to obtain a carbon monoxide oxidation catalyst material.

[0057] Comparative Process 1: Electroplating sludge was mixed with a 3M sulfuric acid solution at a liquid-to-solid ratio of 0.6:1 (mL / g). The mixture was ultrasonically stirred for 40 minutes at a frequency of 45kHz in an ultrasonic cleaner, followed by settling for 2 hours. The supernatant was separated, and the resulting sludge was acid-activated sludge. The acid-activated sludge was then mixed with an 8M sodium hydroxide solution at a liquid-to-solid ratio of 0.6:1 (mL / g) and stirred for 3 hours to obtain alkali-treated sludge. The alkali-treated sludge was placed in a microwave reactor, and microwave activation was performed at a power of 600W for 15 minutes to obtain microwave-activated alkali-treated sludge. Plant extract and microwave-activated alkali-treated sludge were weighed at a mass ratio of 2.5:100, stirred evenly, and then transferred to a hydrothermal reactor. The hydrothermal temperature was set at 220℃ for 12 hours to obtain hydrothermally activated material, wherein the plant extract was hyacinth extract. The hydrothermally activated material was thoroughly washed with deionized water until neutral, then filtered. The filter cake was placed in a drying oven and dried at 60°C for 5 hours to obtain dried hydrothermally activated powder. The dried powder was placed in a molding device and pressed into a catalyst preform with a certain shape and strength under a pressure of 30 MPa. The catalyst preform was placed in a tube furnace and calcined in an air atmosphere at a temperature of 750°C for 6 hours to obtain a carbon monoxide oxidation catalyst material.

[0058] Comparative Process 2: Waste vanadium-titanium catalyst was mixed with a 3M sulfuric acid solution at a liquid-to-solid ratio of 0.6:1 (mL / g). The mixture was ultrasonically stirred for 40 minutes at a frequency of 45kHz in an ultrasonic cleaner, followed by settling for 1.5–2.5 hours. The supernatant was separated, and the resulting sludge was the acid-activated sludge. The acid-activated sludge was mixed with an 8M sodium hydroxide solution at a liquid-to-solid ratio of 0.6:1 (mL / g) and stirred for 3 hours to obtain the alkali-treated sludge. The alkali-treated sludge was placed in a microwave reactor, and microwave activation was performed at a power of 600W for 15 minutes to obtain microwave-activated alkali-treated sludge. Plant extract and microwave-activated alkali-treated sludge were weighed at a mass ratio of 2.5:100, stirred evenly, and then transferred to a hydrothermal reactor. The hydrothermal temperature was set at 220℃ for 12 hours to obtain the hydrothermally activated material, in which the plant extract was hyacinth extract. The hydrothermally activated material was thoroughly washed with deionized water until neutral, then filtered. The filter cake was placed in a drying oven and dried at 60°C for 5 hours to obtain dried hydrothermally activated powder. The dried powder was placed in a molding device and pressed into a catalyst preform with a certain shape and strength under a pressure of 30 MPa. The catalyst preform was placed in a tube furnace and calcined in an air atmosphere at a temperature of 750°C for 6 hours to obtain a carbon monoxide oxidation catalyst material.

[0059] The carbon monoxide oxidation test and carbon monoxide oxidation efficiency calculation were the same as in Example 1. The results of this comparative test are shown in Table 5.

[0060] Table 5. Effects of different comparative processes on the performance of the prepared carbon monoxide oxidation catalyst. Process type Carbon monoxide oxidation efficiency Relative error percentage Inventive process 97.25% ±0.1% Comparative process 1 45.17% ±0.1% Comparative process 2 42.84% ±0.1%

[0061] As shown in Table 5, the carbon monoxide oxidation efficiency achieved by the carbon monoxide oxidation catalyst prepared by the process of the present invention is significantly higher than that of comparative process 1 and comparative process 2, and is higher than the sum of the two.

Claims

1. A method for preparing a carbon monoxide oxidation catalyst using a spent vanadium-titanium-based catalyst and electroplating sludge, characterized by, The method comprises the following steps: (1) taking waste vanadium-titanium catalyst and electroplating sludge, mixing them in a blender to obtain a mixed slurry; (2) mixing the mixed slurry with a sulfuric acid solution, ultrasonic cleaning in an ultrasonic cleaner, then standing and settling, separating the supernatant to obtain acid activated slag; (3) mixing the acid activated slag with a sodium hydroxide solution, stirring to obtain alkali treated slag; (4) microwave activation treatment of the alkali treated slag in a microwave reactor to obtain microwave activated alkali treated slag; (5) taking plant extract and microwave activated alkali treated slag, stirring them to obtain a mixture, then transferring the mixture to a hydrothermal reactor for hydrothermal reaction to obtain hydrothermal activated material; (6) washing the hydrothermal activated material with deionized water until neutral, then performing suction filtration separation, then drying the filter cake in a drying oven to obtain dried hydrothermal activated powder, and then placing the dried hydrothermal activated powder in a molding device to press and form a catalyst blank; (7) placing the catalyst blank in a tube furnace, and calcining under an air atmosphere to obtain a carbon monoxide oxidation catalyst material. 2.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The mass ratio of the waste vanadium-titanium catalyst to the electroplating sludge in step (1) is 40-60:

100. 3.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The stirring speed in step (1) is 500-2500 r / min, and the stirring time is 20-60 minutes. 4.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The concentration of the sulfuric acid solution in step (2) is 2-4 M, and the liquid-solid ratio of the sulfuric acid solution to the mixed slurry is 0.4-0.6:1 (mL / g). 5.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The ultrasonic frequency in step (2) is 35-45 kHz, and the ultrasonic assisted stirring time is 30-40 minutes, followed by standing and settling for 1.5-2.5 hours. 6.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The concentration of the sodium hydroxide solution in step (3) is 4-8 M, the liquid-solid ratio of the sodium hydroxide solution to the acid activated slag is 0.4-0.8:1 (mL / g), and the stirring reaction time is 2-4 hours. 7.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The microwave power in step (4) is 400-600 W, and the microwave time is 5-15 minutes. 8.The method for preparing a carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The mass ratio of the plant extract to the microwave activated alkali treated slag in step (5) is 0.5-2.5:100, the hydrothermal reaction temperature is 180-220°C, and the hydrothermal reaction time is 8-12 hours. 9.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The drying temperature in step (6) is 60-120°C, and the drying time is 5-15 hours. 10.The method for preparing carbon monoxide oxidation catalyst using waste vanadium-titanium catalyst and electroplating sludge according to claim 1, characterized in that, The calcination temperature in step (7) is 550-750°C, and the calcination time is 4-6 hours.

Citation Information

Patent Citations

  • Supported vanadium-titanium synergistic denitration and demercuration catalyst and preparation method thereof

    CN115025772A

  • CO oxidation catalyst taking waste rare earth-based denitration catalyst as raw material and preparation method of CO oxidation catalyst

    CN116037148A

  • Method for preparing low-temperature ammonia-free denitration catalyst by utilizing industrial solid waste

    CN117943128A

  • Separation and extraction method for valuable metals in electroplating sludge

    CN120924793A

  • Carbon monoxide oxidation catalyst

    RU2156164C2

Cited By

  • Method for preparing carbon monoxide oxidation catalyst by using titanium gypsum and waste hydrogenation catalyst

    CN121797361A

  • Method for preparing carbon monoxide normal-temperature oxidation catalyst based on electrolytic manganese residues and landfill leachate

    CN121847199A

  • Method for preparing carbon monoxide normal-temperature oxidation catalyst from electrolytic manganese residues and oil sludge

    CN121869413A